Policing anti-government protests during the coronavirus crisis in Poland - Rak, Joanna (Teorija in praksa, 2021)
This research aims to give insight into the processes of public interaction between the police and antigovernment protesters during the Coronavirus Crisis in Poland by evaluating crowd control mechanisms. It addresses the research question: where does the model of anti-government protest policing developed by the Polish Police during the Covid-19 pandemic lie on a continuum of antinomic ideal types of escalated force and negotiated management? The research is embedded in studies on protest policing and draws on an intertextual qualitative analysis of police statements and media news. It shows that the policing of protests was closer to escalated force. However, a hybrid model was involved that combined elements of coercion and negotiation. In terms of protecting the right to freedom of peaceful assembly and police tolerance for community disruption, this particular form of policing is close to escalated force. Still, the communication between the police and the assembly participants, the extent and manner of the arrests closely mirrored both models. One dimension, the extent and nature of the force used, indicated negotiated management.
Keywords: Covid-19; Epidemics; Epidemije; Police; Policija; policijski nadzor nad protesti; Protesti; Protests; zajezitev